If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4+3)=(-3+1)
We simplify the equation to the form, which is simple to understand
(4+3)=(-3+1)
Simplifying terms in parentheses
(+7)=(-3+1)
Simplifying terms in parentheses
(+7)=(-2)
Remove unnecessary parentheses
+7=(-2)
Remove unnecessary parentheses
+7=-2
We move all terms containing to the left and all other terms to the right.
0=-2-7
We simplify left and right side of the equation.
0=-9
0=-9
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 4x=x+136 | | x=y^3-(13*y) | | 2x^2+4+11x+1=180 | | -3h+12-4=-7h-9-16 | | 2(5+x)+2x=9x | | 2x^2+11x+1=180 | | 5x-2y-8=0 | | -3(4x+1)+6x=4(2x-6) | | 3(m+8)+-10=-1 | | logx+log(x-19)=log(13x) | | (4x)8-3-5=360 | | 27=-13+v | | (6x-20)=(3x+31) | | (x)+(x+1)=35 | | 28x-20=26x+6 | | .4x=-3 | | 16=7+3n | | 27=3(m+5) | | 6x-20=3x+31 | | -15x-20=-14x+35 | | 2x^2+x-6=6 | | 3(x-7)+8=4 | | -6y+9=7y+3 | | x+15=124 | | 4x+8=180 | | -36=6+6x | | 1/3(6g-9)=7-2g | | 12v^2-25v-7=0 | | 2x-16=-3x^2 | | 67x-1=65+3 | | 23+y=1 | | 15=4.3G-2.1(n-4) |